Progressive Islamic Education in the Muhammadiyah Perspective: Implications for Islamic Religious Education Instruction - Wulan Artistika Apriliana; Dartim Dartim (Universitas Muhammadiyah Surakarta, 2025)
This study examines the concept of Progressive Islamic Education from the Muhammadiyah perspective and analyzes its implications for Islamic Religious Education (PAI) learning. Grounded in the reformist thought of K.H. Ahmad Dahlan and the paradigm of Islam Berkemajuan, the study conceptualizes education as a transformative process integrating faith (aqidah), moral integrity (akhlak), rationality, scientific development, and social responsibility. Using a qualitative literature-based approach with philosophical analysis, data were collected from scholarly journals and relevant academic sources on Muhammadiyah and Islamic education, and analyzed through descriptive and thematic methods. The findings indicate that Progressive Islamic Education shifts PAI learning from a doctrinal and cognitive orientation toward a holistic, contextual, and student-centered paradigm that emphasizes critical thinking, ethical awareness, social responsibility, and religious moderation through dialogical pedagogy, active learning, and integrative curriculum design, particularly within the Al-Islam and Kemuhammadiyahan (AIK) framework. This study offers a practical pedagogical framework for implementing Progressive Islamic values in PAI learning through curriculum integration, contextual instruction, holistic assessment, and teacher professional development, contributing theoretically and practically to contemporary Islamic education discourse and the formation of moderate, tolerant, and future-oriented Muslim generations.